Is land grabbing an opportunity or a menace to development in developing countries? Evidence from Ghana. Issue 12 (2nd December 2018) - Alhassan, Suhiyini I.; Shaibu, Mohammed T.; Kuwornu, John K.M.
ABSTRACT: This study examined the developmental effects of land grabbing on farming households' livelihoods and their adaptation strategies. Primary data was collected from 560 randomly selected farming households in seven regions of Ghana using questionnaire and was complemented with key informant interviews and focused group discussions. The Spearman rank correlation was used to determine the relationship between land grabbing and livelihood outcomes while the adaptation strategies of households were analysed qualitatively using descriptive and content analysis. The results revealed that land grabbing has a significant negative relationship with food production, income, social cohesion, health and nutrition of farming households, but had a significant positive relationship with education and employment of farming households. Based on the empirical findings, this study concludes that land grabbing in Ghana is to some extent a threat to development, as the disadvantages outweigh the advantages of the livelihood outcomes of the households that have been affected by these land deals, although it may yield some development opportunities that would yield benefits to the households in the long term. The policy recommendations are presented.